load
load
load
load
load
load
load
load
Sugarcane will be shutting down on June 30, 2018. For more information, .

Transformations of Graphs

Shrink, Stretch, Shifts
a data set by xnity
created February 24, 2016
COPY & EDIT
FAMILY TREE
GraphsEquations of GraphsTerm
f(x) = x^2; g(x) = (x - 2)^2Horizontal Shift Right
f(x) = x^2; g(x) = (x + 2)^2Horizontal Shift Left
f(x) = x^2; g(x) = x^2 + 2Vertical Shift Up
f(x) = x^2; g(x) = x^2 - 2Vertical Shift Down
f(x) = x^2; y = (1/2)* f(x^2)Vertical Shrink
f(x) = x^2; y = 2* f(x^2)Vertical Stretch
f(x) = sqrt(x); g(x) = - sqrt(x)Reflection about the x-axis
f(x) = sqrt(x); g(x) = sqrt(- x)Reflection about the y-axis
f(x) = sin x; g(x) = sin ((1/2)x)Horizontal Stretch
f(x) = sin x; g(x) = sin(2x)Horizontal Shrink
f(x) = x^2; g(x) = (2x^2)Horizontal Shrink
f(x) = x^2; g(x) = (1/2)x^2Horizontal Stretch
y = cf(x); 0 < c < 1Vertical Shrink
y = f(cx); c > 1Horizontal Shrink
y = cf(x); c > 1Vertical Stretch
y = f(cx); 0 < c < 1Horizontal Stretch
y = f(x); y = f(x-c)Horizontal Shift Right
y = f(x); y = f(x-(-c))Horizontal Shift Left
y = f(x); y = f(x) + cVertical Shift Up
y = f(x); y = f(x) - cVertical Shift Down
y = f(x); y = f(-x)Reflection on the Y Axis
y = f(x); y = -f(x)Reflection on the X Axis
Ready to learn about Transformations of Graphs?